GLUTATHION-S-TRANSFERASE M1 AND T1 GENE POLYMORPHISM IN THE INDIGENOUS AND ALIEN POPULATION OF GORNAYA SHORIA - Лузина, Фаина Анисимовна; Дорошилова, Анастасия Викторовна; Гуляева, Ольга Николаевна; Ядыкина, Татьяна Константиновна; Казицкая, Анастасия Сергеевна; Панев, Николай Иванович; Мальцева, Нина Васильевна (Medicine in Kuzbass, 2020)
The paper deals with the study of glutathione-S-transferase M1 and T1 gene polymorphism in indigenous Shor and alien Caucasoid population of Gornaya Shoria of the Kemerovo region in order to identify ethnic specificity in their distribution. Materials and methods. The material was collected in field conditions in 2010-2016 in Gornaya Shoria of the Kemerovo region. Blood sampling was carried out with the filling of «Informed consent» in 345 people. DNA samples were isolated by phenol-chloroform extraction. Polymorphism of GSTM1 and GSTT1 genes was studied by real-time PCR using the reagent kits of SibDNA LLC. Statistical processing of the materials was standard software package SPSS 21.0. Main results. Ethnic features of the distribution of polymorphic variants of GSTM1 and GSTT1 genes in the indigenous Shor and alien Caucasoid population of the south of Kuzbass were revealed. The frequency of deletion polymorphism of GSTM1 and GSTT1 genes were statistically significantly lower among the Shors compared with the alien population of the region (the Shors: GSTM1 0/0 – 0.2318, GSTT1 0/0 – 0.2568, Caucasoid population: GSTM1 0/0 – 0.4464, GSTT1 0/0 – 0.4107). The simultaneous combination of «null» genotypes by two loci in the Shors was 3-4 times less common than in a population of European descent. Conclusion. The results of the study on the frequency of occurrence of allelic variants of GSTM1 and GSTT1 genes in Gornaya Shoria population and the revealed ethnic specificity in their distribution can serve as a population control when studying the associations of these markers with multi-factor diseases in the indigenous and alien population of the region.